Dynamic optimisation of adsorber-bed designs ensuring optimal control - Bau, Uwe; Kirches, Christian (Applied thermal engineering, 2017)
A model-based method is presented to rigorously assess and compare adsorber-bed designs. Starting from an initial design, a dynamic model is developed. The initial design is then varied using the dynamic model to determine the Pareto frontier regarding two objectives: coefficient of performance (COP) and specific cooling power (SCP). To ensure that we assess the intrinsic properties of the design and not effects of poor control, we use dynamic optimisation to determine optimal controls for each design. The obtained Pareto frontier allows to compare the adsorber-bed designs. The proposed method is exemplified in a case study: for a finned-tube design, we assess two major design choices, namely grain size of the adsorbent pellet and fin number. The proposed method is shown to allow for a rigorous and efficient assessment of adsorber-bed designs.